A Simple Multifractal Model for Self-Similar Traffic Flows in High-Speed Computer Networks - San Juan-Urrutia, E (Instituto Politecnico Nacional, 2019)
This paper proposes a multifractal model, with the aim of providing a possible explanation for the locality phenomenon that appears in the estimation of the Hurst exponent in stationary second order temporal series representing self-similar traffic flows in current high-speed computer networks. It is shown analytically that this phenomenon occurs if the network flow consists of several components with different Hurst exponents. © 2019 Instituto Politecnico Nacional. All rights reserved.